Public action by MUCPAZ against gender violence: The case of Ciudad Juárez, Chihuahua - Vázquez González, Norma Leticia (2025)
Introduction: Violence against women is a serious problem worldwide. However, government action in implementing programs to address gender-based violence has not been effective, considering the increase of this phenomenon in countries like Mexico. Objective: The objective of this article is to analyze how MUCPAZ contributes to strengthening women's public action to address gender-based violence problems in the Riveras del Bravo neighborhood of Ciudad Juárez, Chihuahua, Mexico. Method and technique: The methodological design of this research was qualitative and exploratory. The strategy used was the case study and 15 semi-structured interviews were carried out, 8 with women members of Mucpaz and 7 with other key actors, which were analyzed with the help of the Atlas.Ti software. Results: MUCPAZ strengthens public action through training to prevent gender-based violence, understanding the levels of public administration action, and creating internal communication networks. Conclusions: There is a risk that Mucpaz will become a palliative remedy that only contains violence in the short to medium term as part of the traditional patriarchal way of creating policies.